Edukasi hygiene sanitasi peralatan terhadap peningkatan pengetahuan tenaga penjamah makanan pada Instalasi Gizi di Rumah Sakit Meuraxa Banda Aceh - Nurul Makhfirah; Abdul Hadi (Poltekkes Kemenkes Aceh, 2024)
Background: The personal hygiene condition of food handlers is a risk factor for coliform contamination of tableware in restaurants. Food handler personal hygiene that does not meet the requirements has a risk of 14 times will cause contamination of tableware compared to food handler personal hygiene that meets the requirements.Objective: To determine the increase in knowledge of food handlers on hygiene sanitation of processing equipment.Methods: This type of research is quantitative research using quasi-experimental research design with pretest-postest design with control group design. Subjects were 10 handlers and 10 objects of equipment, random sampling. This research was conducted in July - August 2022 at Meuraxa Banda Aceh Hospital. A sample of 10 processing handlers was taken with saturated sampling technique where all workers in the processing section there are 10 people will be taken entirely as samples using T-dependent analysis and in this study also measured the results of isolation of the number of germs on processing equipment in hospital nutrition installations.Results: There is an effect of education on increasing the knowledge of food handlers (p = 0,018) and on reducing the number of germs (p = 0,038).Conclusion: There is an effect of providing education on the level of knowledge of food handlers before and after being given nutrition education. Increased knowledge of food handlers on hygiene and sanitation of food processing equipment.